Brief Report: Association of Quantitative and Topographic Assessment of Heberden's Nodes With Knee Osteoarthritis: Data From the Osteoarthritis Initiative - Kumar, Neil M.; Hafezi‐Nejad, Nima; Guermazi, Ali; Haj‐Mirzaian, Arya; Haugen, Ida K.; Roemer, Frank W.; Demehri, Shadpour (Arthritis & rheumatology (Hoboken, N.J.), 2018)
Objective To determine whether the presence, number, and topography (digit location and symmetry) of Heberden's nodes are associated with the incidence and progression of radiographic osteoarthritis (OA) of the knee. Methods We analyzed 8,023 knees (with 8 years of follow‐up) from the Osteoarthritis Initiative. Cox regression was performed on Heberden's node presence, total number, location, and symmetry (using 2 symmetry index models) obtained at baseline physical examination as well as self‐report of Heberden's node presence for evaluation of association with radiographic knee OA incidence (development of a Kellgren/Lawrence grade of ≥2) and progression (worsening in the medial joint space narrowing score of ≥1). Covariate adjustments relevant to OA outcomes were performed. Results The presence of Heberden's nodes (in 64% of the subjects) at baseline physical examinations, but not subjective self‐report of Heberden's nodes, was associated with radiographic knee OA incidence (hazard ratio [HR] 1.19 and 95% confidence interval [95% CI] 1.001–1.402 [approached statistical significance]). Each additional Heberden's node found on physical examination was associated with knee OA incidence (HR 1.03 [95% CI 1.000–1.054] [approached statistical significance]) and progression (HR 1.04 [95% CI 1.016–1.063]). Knee OA incidence and progression were associated with Heberden's nodes located on the third digit (HR 1.26 [95% CI 1.068–1.487] and 1.18 [95% CI 1.019–1.361], respectively) and first digit (HR 1.186 [95% CI 0.992–1.418] [approached statistical significance] and HR 1.26 [95% CI 1.084–1.453], respectively). Heberden's node symmetry was associated with knee OA incidence (model 1 HR 1.09 [95% CI 0.997–1.185] [approached statistical significance]) and progression (model 2 HR 1.13 [95% CI 1.035–1.234]). Conclusion The number of Heberden's nodes, their locations, and symmetry were associated with knee OA incidence and progression over 8 years.